MILLENNIALS’ INTENTION TO STAY: THE ROLE OF PERSON-ORGANIZATION FIT AND JOB SATISFACTION - Rundhung Ilham Bagus Swastasi; Dina Sartika (Jurnal Bisnis Manajemen, 2021)
The tendency of low Intention to stay among millennial generation employees is an essential concern for an organization. The difference in characteristics from the previous generation is a factor that can be considered. The suitability of individual values and values applied in the organization (P-O Fit) can be a way for organizations to retain and attract millennial generation employees. The primary purpose of this research is to analyze Person-Organization Fit (P-O Fit) and its influence on the intention to stay of millennial employees. Moreover, this study investigates the role of job satisfaction in mediating the relationship between P-O Fit and Intention to stay. Data were collected from 151 millennial employees working in Regional Government Bank located within Bandung. The hypothesized relationships were tested and analyzed using hierarchical regression analysis. The results showed that P-O Fit has a positive and significant effect on intention to stay. Moreover, job satisfaction mediates the relationship between P-O Fit and intention to stay.